2022
DOI: 10.1038/s41598-022-16045-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the effect of gender on the human–machine interaction in level 3 automated vehicles

Abstract: The emergence of the level 3 automated vehicles (L3 AVs) can enable drivers to be completely disengaged from driving and safely perform other non-driving related tasks, but sometimes their takeover of control of the vehicle is required. The takeover of control is an important human–machine interaction in L3 AVs. However, little research has focused on investigating the effect of gender on takeover performance. In order to fill this research gap, a driving simulator study with 76 drivers (33 females and 43 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Furthermore, the TTC is even shorter in older-old adults than in younger-old adults (Li et al, 2021). Other studies showed that the TTC did not differ between the two groups (Li et al, 2019a;Li et al, 2019b). One other study showed a contrary result, with longer TTCs in older drivers than in younger drivers (Körber et al, 2016).…”
Section: Take-over Performancementioning
confidence: 95%
See 4 more Smart Citations
“…Furthermore, the TTC is even shorter in older-old adults than in younger-old adults (Li et al, 2021). Other studies showed that the TTC did not differ between the two groups (Li et al, 2019a;Li et al, 2019b). One other study showed a contrary result, with longer TTCs in older drivers than in younger drivers (Körber et al, 2016).…”
Section: Take-over Performancementioning
confidence: 95%
“…However, four other studies using vehicle speeds of 48 km/h, 96 km/h, and 90km/h in the automated driving phase showed greater steering wheel variability and a higher number of collisions (Li et al, 2018;Li et al, 2019b;Li et al, 2021;Peng & Iwaki, 2020). Only one of the studies in which the speed setting varied showed an impact of the speed setting (88.5 km/h or 104.6 km/h) on maximum lateral offset after the TOR (Favarò et al, 2019).…”
Section: Speedmentioning
confidence: 95%
See 3 more Smart Citations